2003
DOI: 10.1103/physrevlett.91.095502
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Entangled Amorphous Network in Tensile Deformation of Semicrystalline Polymers

Abstract: Being composed of crystalline lamellae and entangled amorphous polymeric chains in between, semicrystalline polymers always show a complicated deformation behavior under tensile deformation. In recent years, the process of tensile deformation was found to exhibit several regimes: intralamellar slipping of crystalline blocks occurs at small deformation whereas a stress-induced crystalline block disaggregation-recrystallization process occurs at a strain larger than the yield strain. The strain at this transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
332
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(345 citation statements)
references
References 19 publications
13
332
0
Order By: Relevance
“…In addition, L pf increases with increasing T d . These findings are in perfect agreement with the melting-recrystallization concept already observed for various semi-crystalline polymers [49][50][51].…”
Section: Resultssupporting
confidence: 81%
“…In addition, L pf increases with increasing T d . These findings are in perfect agreement with the melting-recrystallization concept already observed for various semi-crystalline polymers [49][50][51].…”
Section: Resultssupporting
confidence: 81%
“…1,[19][20][21][22][23] The behavior of the polymers during stretching is generally influenced by both the crystalline and the amorphous phases. 12,[24][25][26][27][28] The small-deformation properties are found to depend only on the nature of crystalline lamellae; whereas the ultimate properties are dominated by the entangled amorphous network. 11,13,25 Poly(ε-caprolactone) (PCL) is a biodegradable polymer, which can form homogeneous mixtures in the melt and solution with a wealth of other noncrystallizable compounds, including poly(vinyl methyl ether) (PVME), 24,29 poly(styrene-co-acrylonitrile), 30,31 and poly(vinyl chloride).…”
Section: Introductionmentioning
confidence: 99%
“…12,[24][25][26][27][28] The small-deformation properties are found to depend only on the nature of crystalline lamellae; whereas the ultimate properties are dominated by the entangled amorphous network. 11,13,25 Poly(ε-caprolactone) (PCL) is a biodegradable polymer, which can form homogeneous mixtures in the melt and solution with a wealth of other noncrystallizable compounds, including poly(vinyl methyl ether) (PVME), 24,29 poly(styrene-co-acrylonitrile), 30,31 and poly(vinyl chloride). 32,33 PCL is, therefore, a natural candidate to investigate the effect of blending on the mechanical properties and deformation behavior, thus providing new insight into the role of the entangled amorphous phase in the tensile deformation of semicrystalline polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men et al [34] has shown that this critical stress is in connection with the intrinsic stability of crystals, which is related to their theoretical equilibrium melting temperature. The low melting temperature of PCL leads to the deformation of crystallites at lower stresses, compared to other semi-crystalline polyolefins, polyesters and this also helps to minimize the cold-drawing and orientation of amorphous network.…”
mentioning
confidence: 99%